A rare polyclad genus Bulaceros (Platyhelminthes: Polycladida: Pseudocerotidae): new species and new record from Indian coral atolls. Issue 8 (20th October 2020) - Dixit, Sudhanshu; Manjebrayakath, Hashim; Saravanane, N.
ABSTRACT: The genus Bulaceros (Polycladida: Pseudocerotidae) erected by Newman & Cannon (1996) is a rare genus found only in the Pacific Ocean and is known by only one species, Bulaceros porcellanus Newman & Cannon, 1996 so far. The present work, based on collection from the Lakshadweep Islands, which are the only coral atolls in India, describes a second species Bulaceros newcannorum sp. nov. under this genus and also reports the occurrence of Bulaceros porcellanus for the first time from the Indian Ocean. Bulaceros newcannorum sp. nov. is described based on external and internal morphology supported with histological studies and photographs of external and internal details. Bulaceros newcannorum sp. nov. is characterized by knobbed pseudotentacles with white tips, translucent background with brown gut diverticula, darker medially, irregular white spots on the dorsum, margin of white spots and submarginal band in a mixture of brown and black. This is the first report of the genus Bulaceros from the entire Indian Ocean region. Publication LSID : lsid:http://zoobank.org:pub:C8FA7FDA-A7AF-4AD9-8AE2-23ADD9FDEB31